The Influence of Service Quality, Emotional Marketing and Spiritual Marketing On Customer Satisfaction - et.al, Ida Hindarsah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of service quality, the influence of emotional marketing, the effect of spiritual marketing, on satisfaction, and to know the three variables jointly affect customer satisfaction. This research is a quantitative research. With a questionnaire instrument distributed to 90 customers. Statistical test using classical assumption test, hypothesis testing using regression analysis test multiple test T test, F test and R test the coefficient of determination. The results showed that service quality, emotional marketing and spiritual marketing each had a significant positive effect on customer satisfaction. Then the quality of service, emotional marketing and spiritual marketing simultaneously have an effect on satisfaction